Distribusi Fonem Vokal Buku Teks Bahasa Indonesia Kelas 1 Sekolah Dasar - Rakhmat, Muhammad; Alhariri, Sopia; Annursiah, Sena; Nurhasanah, Heti; Rahmatillah, Yulia; Wachyudin, Wachyudin (ppjbsip, 2024)
This study contains research on the analysis of the distribution of vowel phonemes in the reading material of grade 1 elementary school textbooks. The research is based on the rampant language errors in the field of pronunciation. These errors are caused by ignorance of good and correct pronunciation. So this research aims to introduce the pronunciation through the distribution of vowel phonemes in a word in the smallest community environment, namely schools. The phoneme distribution analysis in this study uses the theory of phonetic transcription, vowel classification, and distribution of Indonesian phonemes. The method used is descriptive qualitative. The results of the analysis show that the reading material in the textbook contains ten phonological symbols in the form of [a, i, ?, u, U, e, ?, ?, o, ?]. The ten symbols are pronounced in different ways based on the sound organs they use. The vowel phoneme that always appears in the reading material is the sound [a] which dominates the appearance at the beginning of the word, the middle of the word, and the end of the word.AbstrakPenelitian ini berisikan analisis distribusi fonem vokal dalam bahan bacaan buku teks kelas 1 Sekolah Dasar. Penelitian ini didasari oleh maraknya kesalahan berbahasa dalam bidang pelafalan. Kesalahan tersebut disebabkan oleh ketidaktahuan mengenai cara pelafalan yang baik dan benar. Sehingga penelitian ini bertujuan untuk mengenalkan cara pelafalan melalui pendistribusian fonem vokal dalam suatu kata di lingkungan masyarakat terkecil yaitu sekolah . Analisis distribusi fonem pada penelitian ini menggunakan teori transkripsi fonetik, klasifikasi vokal, dan distribusi fonem bahasa Indonesia. Metode yang digunakan berupa kualitatif deskriptif. Hasil analisis menunjukkan bahwa bahan bacaan dalam buku teks tersebut terdapat sepuluh lambang fonologi berupa [a, i, ?, u, U, e, ?, ?, o, ?]. Dari sepuluh lambang tersebut dilafalkan dengan cara yang berbeda berdasarkan pada organ bunyi yang digunakannya. Fonem vokal yang selalu muncul dalam bahan bacaan tersebut ialah bunyi [a] yang mendominasi kemunculan pada awal kata, tengah kata, dan akhir kata.